2017
DOI: 10.1242/jcs.207134
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of the CIF1–CIF2 complex in trypanosomes identify the structural motifs required for cytokinesis

Abstract: Cytokinesis in trypanosomes occurs uni-directionally along the longitudinal axis from the cell anterior towards the cell posterior and requires a trypanosome-specific CIF1-CIF2 protein complex. However, little is known about the contribution of the structural motifs in CIF1 and CIF2 to complex assembly and cytokinesis. Here, we demonstrate that the two zinc-finger motifs but not the coiled-coil motif in CIF1 are required for interaction with the EF-hand motifs in CIF2. We further show that localization of CIF1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…S4C) or interaction with any of the known or unknown CIF1-interacting proteins, respectively. It is noteworthy that two previously identified CIF1-interating proteins, TbAUK1 and CIF2, are also recruited by CIF1 to the new FAZ tip at late anaphase and S phase, respectively (12,15). However, localization of the CIF1interacting protein CIF3 to the new FAZ tip is independent of CIF1, but the stability of CIF3 depends on the formation of the CIF1-CIF3 complex (14).…”
Section: Cif1 Is a Master Regulator Of Cytokinesismentioning
confidence: 96%
See 3 more Smart Citations
“…S4C) or interaction with any of the known or unknown CIF1-interacting proteins, respectively. It is noteworthy that two previously identified CIF1-interating proteins, TbAUK1 and CIF2, are also recruited by CIF1 to the new FAZ tip at late anaphase and S phase, respectively (12,15). However, localization of the CIF1interacting protein CIF3 to the new FAZ tip is independent of CIF1, but the stability of CIF3 depends on the formation of the CIF1-CIF3 complex (14).…”
Section: Cif1 Is a Master Regulator Of Cytokinesismentioning
confidence: 96%
“…However, precisely how CIF1 stability is maintained by KPP1 remains unknown. Previous studies demonstrated that formation of the CIF1-CIF2 protein complex is necessary for maintaining CIF1 stability (13,15). It is thus possible that KPP1 may play a role in promoting CIF1-CIF2 complex assembly.…”
Section: Cif1 Is a Master Regulator Of Cytokinesismentioning
confidence: 99%
See 2 more Smart Citations
“…Regulation of the unusual cytokinesis in T. brucei is orchestrated by a novel signaling pathway composed of two evolutionarily conserved proteins kinases, the Polo‐like kinase homolog TbPLK and the Aurora B kinase homolog TbAUK1, and a cohort of trypanosome‐specific regulators, which act at the distal tip of the new FAZ and/or the cleavage furrow to drive cytokinesis initiation and furrow ingression (Li and Wang, 2006; Li et al ., 2009; McAllaster et al , ; Zhou et al , ; ; ; ; Hu et al , ; Hilton et al , ; Kurasawa et al , ). Among these trypanosome‐specific regulators are three cytokinesis initiation factors named CIF1, CIF2, and CIF3 (Zhou et al , ; ; Hu et al , ; Kurasawa et al , ). CIF1 and CIF2 are interdependent for maintaining their respective protein stability (Zhou et al , ), whereas CIF1 maintains CIF3 protein stability and CIF3 recruits CIF1 to the new FAZ tip (Kurasawa et al , ).…”
Section: Introductionmentioning
confidence: 99%